Tumor Microenvironment: Lactic Acid Promotes Tumor Development - Yuting Gao; Hao Zhou; Gege Liu; Junlu Wu; Yi Yuan; Anquan Shang (Journal of Immunology Research)
Lactic acid is a “metabolic waste” product of glycolysis that is produced in the body. However, the role of lactic acid in the development of human malignancies has gained increasing interest lately as a multifunctional small molecule chemical. There is evidence that tumor cells may create a large amount of lactic acid through glycolysis even when they have abundant oxygen. Tumor tissues have a higher quantity of lactic acid than normal tissues. Lactic acid is required for tumor development. Lactate is an immunomodulatory chemical that affects both innate and adaptive immune cells’ effector functions. In immune cells, the lactate signaling pathway may potentially serve as a link between metabolism and immunity. Lactate homeostasis is significantly disrupted in the TME. Lactate accumulation results in acidosis, angiogenesis, immunosuppression, and tumor cell proliferation and survival, all of which are deleterious to health. Thus, augmenting anticancer immune responses by lactate metabolism inhibition may modify lactate levels in the tumor microenvironment. This review will evaluate the role of lactic acid in tumor formation, metastasis, prognosis, treatment, and histone modification. Our findings will be of considerable interest to readers, particularly those engaged in the therapeutic treatment of cancer patients. Treatments targeting the inhibition of lactate synthesis and blocking the source of lactate have emerged as a potential new therapeutic option for oncology patients. Additionally, lactic acid levels in the plasma may serve as biomarkers for disease stage and may be beneficial for evaluating therapy effectiveness in individuals with tumors.